Gendered and Embodied Un/learning among Women Disengaging from Faith in the UK and Finland - van den Brandt, Nella; Rantala, Teija (Approaching Religion, 2024)
Women often embody the central values and practices of their religious tradition. When they leave their community, women find a part of the “religious tapestry” remaining with them long after their disengagement. In this article, we draw from research in the UK and Finland to explore women’s efforts to unlearn parts of their former religious belonging. We draw on in total thirty-five interviews with women who disengaged from the Mormon Church, Jehovah’s Witnesses and Conservative Laestadianism. We conceptualize un/learning as a multi-layered process consisting of both un-learning and re-learning. We explore women’s narratives about negotiating bodily limits, conduct and belonging, and understand these as suggesting experiences of a threefold un/learning: gendered, spatial-social and epistemic. We argue that examining gendered and embodied un/learning helps to understand women’s disengagement processes from minority Christian traditions in Western and Northern European secularized contexts such as the UK and Finland.